Collaborative learning in economics: Do group characteristics matter?. (May 2019) - Liverpool-Tasie, Lenis Saweda O.; Adjognon, Guigonan Serge; McKim, Aaron J.
Abstract: While the positive impacts of collaborative learning are well recognized, relatively little is known about how group characteristics (e.g., group size and composition) affect learning outcomes. Consequently, this article explores how group characteristics affect learning. We leverage a random assignment of students into groups of predetermined sizes to explore the effect of group size on learning outcomes in an undergraduate economics class. Though confirming the benefits of collaborative learning, our results indicate smaller group sizes (i.e., groups of about 5 or 6 members) are preferred to enhance learning, in our study context. We also find group learning effects tend to be limited for students with cultural and/or language barriers that limit participation. This is an important consideration for many US institutions with increasing enrollments of international students, particularly from Asian countries.